2002
DOI: 10.1007/s001920200024
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal Erosion of Cadaveric Fascia Lata following Abdominal Sacrocolpopexy and Suburethral Sling Urethropexy

Abstract: The aim of this paper is to report vaginal erosion of cadaveric fascia lata used for abdominal sacrocolpopexy and suburethral sling urethropexy. The charts of patients who underwent abdominal sacrocolpopexy or suburethral sling urethropexy between March 1994 and February 1999 were reviewed for perioperative data. In 47 cases of abdominal sacrocolpopexy or suburethral sling, 32 utilized cadaveric fascia lata, with 11 for sacrocolpopexy and 22 for suburethral sling. Vaginal erosion of cadaveric fascia lata graft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 6 publications
1
11
0
1
Order By: Relevance
“…These data were not combined with subjective The observation that there may be detectable differences between the groups potentially attributable to the choice of material is underscored by the fact that the only two profound failures (resulting in recurrence of total vaginal vault prolapse) occurred in the fascia lata group. Our report of potential insufficiency of allogeneic fascia lata is consistent with other reports that have suggested that radiated and processed cadaveric fasciae latae for gynecologic reconstructive procedures are unsatisfactory due to either autolysis noted at reoperation or erosion [17,19,30]. Fitzgerald and her colleagues have reported in both human [19,30] and canine [31] models that most of the recovered grafts, when recoverable, do not show histologic evidence of organization into load-bearing structure.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…These data were not combined with subjective The observation that there may be detectable differences between the groups potentially attributable to the choice of material is underscored by the fact that the only two profound failures (resulting in recurrence of total vaginal vault prolapse) occurred in the fascia lata group. Our report of potential insufficiency of allogeneic fascia lata is consistent with other reports that have suggested that radiated and processed cadaveric fasciae latae for gynecologic reconstructive procedures are unsatisfactory due to either autolysis noted at reoperation or erosion [17,19,30]. Fitzgerald and her colleagues have reported in both human [19,30] and canine [31] models that most of the recovered grafts, when recoverable, do not show histologic evidence of organization into load-bearing structure.…”
Section: Discussionsupporting
confidence: 79%
“…While there are several reports of successful use of allogeneic fascia lata for suburethral slings [13,14] and the use of other alternative materials (including autologous rectus fascia) for ASC [10,15,16], there are few preliminary studies to otherwise support the use of allogeneic fascia lata for ASC [17,18]. Because gynecologic use differs significantly from orthopedic use, there is cause for concern that this cadaveric fascia lata may not provide long-term vaginal support.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The abdominal sacrocolpopexy suspends the prolapsed upper vagina to the anterior ligament of the sacrum by utilizing a ''bridging'' material which may include harvested or cadaveric allograft, treated xenograft, or synthetic materials such as polytetrafluoroethylene (PTFE-Goretex), and polypropylene (Mersilene, Prolene.) Erosions into the vagina are reported with both synthetic as well as tissue grafts [2]. Erosions can be initially managed with antibiotics, vaginal estrogen, partial revision of the protruding or infected material, or complete removal of the graft.…”
Section: Introductionmentioning
confidence: 99%
“…Cadaveric allografts and xenografts were originally considered more biocompatible than synthetic materials, and, consequently, erosion and extrusion have been considered uncommon. In recent reports, however, it appears that no material is immune to vaginal extrusion, as this complication has been identified after implantation of cadaveric fascia lata and cadaveric dermal allografts [7,8]. In addition, significant rates of extrusion and infectious complications have been identified with certain xenografts, including bovine pericardium and eightply porcine small intestinal submucosa [9,10].…”
Section: Discussionmentioning
confidence: 99%